INHERITANCE LEGAL SYSTEM IN INDONESIA: A LEGAL JUSTICE FOR PEOPLE - Barlinti, Yeni Salma (Indonesia Law Review, 2013)
As one of Asian countries, Indonesia has varied of cultures and religions. This variety affects positive laws in Indonesia, one of them is inheritance law. Indonesia has three inheritance legal systems, that is, adat inheritance law, Islamic inheritance law, and western inheritance law. Adat inheritance law is a norm of local adat community about inheritance. Islamic inheritance law is a norm of inheritance based on al Qur’an (Islamic holy book) and hadis (words, acts, and silence of Prophet Muhammad PBUH). In Indonesia, there are three schools of Islamic inheritance law, that is, Syafi’i’s (patrilineal) system of inheritance law (Imam Syafi’i is the most influenced school for Indonesian people), Hazairin’s (bilateral) system of inheritance law (Hazairin was Profesor at University of Indonesia had different view from Imam Syafi’i), and Compilation of Islamic Law system of inheritance law (Compilation of Islamic Law is Islamic law written by Indonesian ulama and Islamic experts). The last, western inheritance law is a norm of heritage based on Burgerlijk Wetboek as legal product of Dutch government when occupied Indonesia. All three inheritance legal systems are available for Indonesian people. We are able to know the availability of these systems is from legal cases in the courts, civil court and religious court. On the paper will be explained comparison of three systems of inheritance law, legal subject using the system (personality principle), and implementation of the system in the courts.